Male and Female Students’ Use of Textual Discourse Markers in Writing Academic Essays - Pasaribu, Truly Almendo (Journal of Language and Literature, 2017)
Growing discussion related to gender differences and language includes studies on discourse markers. Not only do these markers play an important role in spoken communication, but they are also important in written one. Previous studies (Tse & Hyland, 2008; Yeganeh and Ghoreyshi, 2015) reveal that there are some discrepancies among scholar whether gender differences influence the use of language, including the choice of discourse markers. Moreover, gender differences and the use of textual discourse markers by Indonesian EFL students in EFL essays have not been extensively discussed. Therefore, this study aimed at elaborating the use of textual discourse markers in male and female students’ essays. This study involved 40 essays, 20 essays written by female students and 20 essays written by male students. Those essays were selected randomly from Critical Reading and Writing 1 (CRW 1) courses. The study aimed at analyzing the differences and similarities in the use of discourse markers between female and male students’ essays based on Fraser’s classifications (1999) of textual discourse markers. Finally, this research concluded the discussion by giving some implication which can be applied in writing classes.Keywords: gender, writing essays, discourse markers